1982
DOI: 10.1523/jneurosci.02-10-01439.1982
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol receptor levels in rat hypothalamic and limbic nuclei

Abstract: The amount of cytoplasmic receptor for the steroid hormone, estradiol (E2), was determined in 46 nuclei and subdivisions of rat brain. Individual nuclei were removed from 300-micrometers frozen sections according to the punch-out method of Palkovits (Palkovits, M. (1973) Brain Res. 59: 449-450), and the content of E2 receptor was measured with a sensitive radioligand binding method. Cytoplasmic receptors for E2 were distributed heterogeneously throughout the rat brain. The highest level of receptor (40 fmol/mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(30 citation statements)
references
References 26 publications
3
26
1
Order By: Relevance
“…Comparison of our present data with that presented for estrogen receptors in our companion paper (Rainbow et al, 1982b) suggests, but does not prove, that some brain regions which contain estrogen receptors lack the capacity to form progestin receptors in response to Ez. For example, both the medial and cortical amygdala contain estrogen receptors, but only the medial amydala shows a significant CPR induction following EZ treatment.…”
Section: Methodscontrasting
confidence: 89%
See 1 more Smart Citation
“…Comparison of our present data with that presented for estrogen receptors in our companion paper (Rainbow et al, 1982b) suggests, but does not prove, that some brain regions which contain estrogen receptors lack the capacity to form progestin receptors in response to Ez. For example, both the medial and cortical amygdala contain estrogen receptors, but only the medial amydala shows a significant CPR induction following EZ treatment.…”
Section: Methodscontrasting
confidence: 89%
“…This concentration of C3H] R5020 was selected to bind specifically the high, but not low, affinity progestin binding site present in brain . Bound [3H]R5020 was measured by gel filtration on "miniature" Sephadex LH-20 (Pharmacia) columns as described in our companion paper (Rainbow et al, 1982b).…”
Section: Methodsmentioning
confidence: 99%
“…What is the mechanism by which a previously unresponsive neuronal type becomes responsive? Although estrogens can act to alter gene transcription (McEwen et al, 1978), it is unlikely that this is the case in the present study because in the hippocampus, both ␣-and ␤-estrogen receptors have been identified on interneurons and glial cells and not on dentate granule cells (Rainbow et al, 1982;L oy et al, 1988;Pelletier et al, 1988;Weiland et al, 1996;Kuiper et al, 1997;Li et al, 1997). Estradiol might act directly on membranes, altering their properties to induce glutamate release, thus increasing intraneuronal calcium, stimulating NMDA receptors, leading to the addition of dendritic spines (Parpura et al, 1994;Woolley and McEwen, 1994;K lintsova et al, 1995).…”
Section: Discussionmentioning
confidence: 63%
“…However, several animal studies in the literature discuss regionally specific trophic effects induced by the introduction of gonadal steroid hormones (for a review, see Jones, 1988). Some of the highest concentrations of steroid hormone receptors in rats are found in the hippocampus, amygdala, hypothalamus, and septal nuclei (Rainbow, Parsons, McLusky, & McEwen, 1982;Stumph & Sar, 1978), all of which are within our anterior diencephalic and MTL regions. Perhaps the increase in circulating gonadal steroid hormones that occurs at puberty has organizational effects on the morphology of the human brain.…”
Section: Asymmetry Analysesmentioning
confidence: 99%